2020
DOI: 10.1109/access.2020.2989739
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Detection Techniques of Insider Threat Incidents

Abstract: Vital organizations have faced increasing challenges of how to defend against insider threats that may cause a severe damage to their assets. The nature of insider threats is more challenging than external threats, as insiders have a privileged access to sensitive assets of an organization. In fact, there are several studies that reviewed the insider threat detection approaches from taxonomical and theoretical perspectives. However, the protection against insider threat incidents requires empirical defense sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The relevance of behavioral information security, as defined by the author, is concerned with users' behavior in protecting information through the use of antimalware software, data backup, and secure wireless networks. The authors also mentioned data collecting and measurement solutions that are available to provide exclusive access to authorized individuals alone [58]. Stahl et al [59] investigated the significance of information security policies, and looked at examples of them in the healthcare industry.…”
Section: Information Security Policiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance of behavioral information security, as defined by the author, is concerned with users' behavior in protecting information through the use of antimalware software, data backup, and secure wireless networks. The authors also mentioned data collecting and measurement solutions that are available to provide exclusive access to authorized individuals alone [58]. Stahl et al [59] investigated the significance of information security policies, and looked at examples of them in the healthcare industry.…”
Section: Information Security Policiesmentioning
confidence: 99%
“…Aviation [25,58] • Mechanisms for preventing illegal access to aviation services or airport areas by managing access control and providing authentication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several case studies of organizations failures, with respect to insider threats, can be found in [4]. The studies in [17][18][19] reviewed the literature of the insider threat detection area from different perspectives. For example, cybersecurity issues related to insider threats, such as advanced persistent threats and malware, are reviewed in [17], while a classification of the insider threat research is demonstrated in [18].…”
Section: Related Workmentioning
confidence: 99%
“…For example, cybersecurity issues related to insider threats, such as advanced persistent threats and malware, are reviewed in [17], while a classification of the insider threat research is demonstrated in [18]. The study in [19], categorized and compared different empirical techniques for insider threat detection in terms of 10 significant factors (e.g., datasets, feature domains, classification techniques, simulated scenarios, performance and accuracy metrics, etc.). It highlights the factors that reflect the methodology and performance of reviewed approaches from various empirical perspectives.…”
Section: Related Workmentioning
confidence: 99%